2018
DOI: 10.1016/j.jagp.2018.03.016
|View full text |Cite
|
Sign up to set email alerts
|

People's Beliefs and Expectations About How Cognitive Skills Change with Age: Evidence From a U.K.-Wide Aging Survey

Abstract: Results suggest that people are less aware of the potential cognitive benefits of certain activities, such as exercise and diet. It is important to build awareness about the benefits of lifestyles and activities for cognitive health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
31
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(38 citation statements)
references
References 15 publications
5
31
2
Order By: Relevance
“…Having the kind of genes to age successfully was important to over 60% of respondents and being able to make lifestyle choices affecting how we age was important to over 85% of respondents (Phelan et al, 2004). Surveys on brain health in the UK and USA found that more than 9 in 10 respondents believe cognitive skills can be improved with age (AARP, 2015;Vaportzis & Gow, 2018). While knowledge of potentially beneficial lifestyle factors varied, those rated as most important to maintaining or improving cognitive skills from the UK survey included having a sense of purpose, eating a healthy diet, challenging the mind, getting adequate sleep, and keeping physically active (Vaportzis & Gow, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Having the kind of genes to age successfully was important to over 60% of respondents and being able to make lifestyle choices affecting how we age was important to over 85% of respondents (Phelan et al, 2004). Surveys on brain health in the UK and USA found that more than 9 in 10 respondents believe cognitive skills can be improved with age (AARP, 2015;Vaportzis & Gow, 2018). While knowledge of potentially beneficial lifestyle factors varied, those rated as most important to maintaining or improving cognitive skills from the UK survey included having a sense of purpose, eating a healthy diet, challenging the mind, getting adequate sleep, and keeping physically active (Vaportzis & Gow, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Surveys on brain health in the UK and USA found that more than 9 in 10 respondents believe cognitive skills can be improved with age (AARP, 2015;Vaportzis & Gow, 2018). While knowledge of potentially beneficial lifestyle factors varied, those rated as most important to maintaining or improving cognitive skills from the UK survey included having a sense of purpose, eating a healthy diet, challenging the mind, getting adequate sleep, and keeping physically active (Vaportzis & Gow, 2018). Although people recommended many of those lifestyles and behaviours to others to improve or maintain their cognitive skills with age (Niechcial et al, 2019) and reported engaging in many of them, they rarely did so to specifically benefit their cognitive skills (AARP, 2015;Vaportzis & Gow, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…One main aspect of age-related health problems is cognitive deterioration. While most people think it is possible to prevent cognitive impairment due to ageing, a lot of them are not sure how to do so (Vaportzis & Gow, 2018). Alongside with physical exercise and improvement in healthcare, nutrition has gotten into focus as a contributor in achieving this goal.…”
Section: Introductionmentioning
confidence: 99%